Asteraceae da Estação Ecológica do Panga, Uberlândia, Minas Gerais - Hattori, Eric Koiti Okiyama (2009)
The Cerrado biome is actually considered one of the 25 hotspots to conservation, due to its high level of occupation and exploration. It has a distinct flora, since it is composed by numerous kinds of physiognomies, since grassland until forest vegetation. The knowledge of the flora of Cerrado is predominantly woody,while the herbaceous component, although higher in proportion, is less known. This is evident by the low number of works realized in this component. The Asteraceae due to its high richness of species, and possess high representation in the herbaceous component of the biome, have not much works in floristic and phytogeography. Even thus, the studies in floristic are predominantly on campos rupestres of Minas Gerais, Goiás and Bahia states. To areas of cerrados, this kind of work is still scant, as the same of phytogeographic studies. Thus, the objective of this dissertation is present the list of species of Asteraceae from Panga Ecological Station, Uberlandia, Minas Gerais. Moreover, is presented a systematic treatment to these species, with a key of identification, morphologic description of each species, comment about geographic distribution, physiognomies where they occur and data about phenology. The phytogeographic approach consist on distribution of these species in Brazil and South America, and with this, to detect the patterns of distribution. 98 species in 46 genera of Asteraceae are presented, and Vernonia (20 spp.), Chromolaena (10 spp.) and Baccharis (8 spp), where the most representative genera in the study area. The grassland and savanic physiognomies presented the majority of species. Although the Panga Ecological Station don´t present none new species to science, two species deserve special attention. Chromolaena brunneola and Chromolaena perforata are restrict to Minas Gerais state. Majority of the species possess wide distribution along the Centro-Oeste region, Sao Paulo, Parana and Bahia states. When is talked about geographical floristic similarities, the Panga Ecological Station, in context of Triangulo Mineiro , has a tendency of higher affinity with the Minas Gerais and Centro-Oeste, mainly in south and west regions of Goias state. This agrees with some results presented previously to the Asteraceae, or even works of woody component in the Cerrado biome.